STUDI EKSPERIMENTAL PENGARUH PENAMBAHAN BACK SPOILER MODEL NACA 0015 TERHADAP KARAKTERISTIK AERODINAMIKA PADA MOBIL MERCEDES BENZ SLK 320 - -, Syamsuri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Generally a vehicle moving against fluid stream will get aerodynamic force. A vehicle must have a high performance to be up against aerodynamic force, these forces will effect its response and stability especially when the vehicle running fast. Stability parameter is determined by the value of lift coefficient or Cl of vehicle. In addition, it is also expected to have minimum drag coefficient or CD. The value of both coefficients can be described through flow characteristics around the vehicle. Aerodynamic force is most affected by drag force and lift force that dependent to the vehicle contour. The aerodynamic performance can be controlled by modifying the characteristic of the vehicles, either one is modifying vehicle body. This study learns adding naca 0015 back spoiler to the Mercedes Benz slk 320. A model type sedan of 1 : 18 scale is tested on wind tunnel under conditions velocity flow 8 m/s, 10 m/s, 12 m/s, 14 m/s, 14 m/s, 16 m/s, 18 m/s and angle of airfoil 00, 50, 100, 150, 200, 250. by adding naca 0015 back spoiler to the Mercedes Benz SLK 320 vehicle will reduce the drag force and lift force so it gets a better characteristic aerodynamic performance. Pressure distribution of the flow was observed centre line of upper and beside right and left of the model vehicle. Result of the experiment indicated that instalment of spoiler NACA 0015 did not influence significantly the pressure distribution on the model. And the result of this research shows that additional accessory has a unique effect on the aerodynamic force